Peran Kepemimpinan Kyai Dalam Mendidik Dan Membentuk Karakter Santri Yang Siap Mengabdi Kepada Masyarakat - Kurniati, Mia; Surur, Miftahus; Rasyidi, Ahmad Hafas (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2019)
Boarding school is an Islamic institution that has a noble goal, that is to educate the community in which is called santri, so that it becomes a human being beneficial to himself more for the outside community. To be a students who hope to be able to be useful in the midst of society, for that institution of boarding schools create a variety of programs and education either in the form of character education and formal education in order to adapt themselves With the demands of the epoch but still on the line of provisions taught his religion that is Islam. In a boarding school certainly has leaders who lead the entire students therein, as the caretaker as well as the main leader of boarding school is a major role in realizing the vision and mission of boarding schools, because only the top The entire activity will run.The method used in this study is a qualitative method in which the source of results is obtained from interviews with predetermined sources. The results of the study prove that the role of the kyai is very urgent for the life of the boarding school community in it,because the kyai is the leader of the boarding school. In realizing a common goal in educating and shaping the character of santri as needed in the midst of society, of course there are several obstacles. However, this is still a reasonable limit and is handled jointly by the kyai together with the administrators of the Salafiyah Dawuhan Islamic boarding school.